The Influence of Organizational Culture on Employee Performance Through Job Satisfaction as an Intervening Variable at The Kendari City Pupr Office - Nur, Muh.; Angi, Robby Daud; Yuana , Indira (Riviera Publishing, 2025)
This study aims to empirically test and explain (1) The influence of organizational culture on employee performance; (2) The influence of organizational culture on employee job satisfaction; (3) The influence of job satisfaction on employee performance; (4) The influence of organizational culture on performance through employee job satisfaction. The population in this study was 105 people who were Civil Servants of the Public Works and Public Housing Department of Kendari City. The sampling technique was census, namely all populations were sampled, namely 105 people. The data analysis method used was Structural Equation Modeling (SEM). The results of the study show that (1) Organizational culture has a positive and significant effect on employee performance; (2) Organizational culture has a positive and significant effect on job satisfaction; (3) Job satisfaction has a positive and significant effect on performance; (4) Organizational culture has a positive and significant effect on employee performance through job satisfaction.